2017
DOI: 10.3164/jcbn.16-89
|View full text |Cite
|
Sign up to set email alerts
|

Compound 48/80, a mast cell degranulator, causes oxidative damage by enhancing vitamin C synthesis via reduced glutathione depletion and lipid peroxidation through neutrophil infiltration in rat livers

Abstract: In this study, we examined whether compound 48/80 (C48/80), a mast cell degranulator, causes hepatic oxidative damage in rats. Serum and liver biochemical parameters were determined 0.5, 3 or 6 h after a single treatment with C48/80 (0.75 mg/kg). Serum histamine and serotonin levels increased 0.5 h after C48/80 treatment but diminished thereafter. Increases in serum vitamin C (VC) and transaminases and hepatic hydrogen peroxide, lipid peroxide, and myeloperoxidase levels and a decrease in hepatic reduced gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…C48/80 has been used to produce experimental anaphylactic shock, because this compound is known to increase histamine release from plasma or tissue (22,23) and an additional nitric oxide release from endothelial cells (24). Our data showed that this compound was effective in inducing anaphylactic shock in rats since blood pressure decreased after C48/80 administration.…”
Section: Discussionmentioning
confidence: 57%
“…C48/80 has been used to produce experimental anaphylactic shock, because this compound is known to increase histamine release from plasma or tissue (22,23) and an additional nitric oxide release from endothelial cells (24). Our data showed that this compound was effective in inducing anaphylactic shock in rats since blood pressure decreased after C48/80 administration.…”
Section: Discussionmentioning
confidence: 57%
“…It is known, for example, that ROS participate in mast cell intracellular signaling [77] and that mast cell degranulators such as acrolein, for example, are able to promote ROS generation [78]. In addition, it was recently demonstrated that Ket was able to control the oxidative damage determined by the compound 48/80, which is a well-known mast cell activator, in rat livers [79]. We also found out that the inflammasome platform was significantly downregulated by Ket therapy, as indicated by reduced levels of NLRP3, caspase-1 and IL-1β mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…McNeil et al (2015), identified that C48/80 could target MRGPRX2 to activate mast cells. Some other research also indicated that C48/80 could induce itch (Dondalska et al, 2020) and cause hepatic oxidative damage (Ohta et al, 2017) or oxidative stress (Kaida et al, 2010). Similar to C48/80, SP is identified as an agonist of MRGPRX2 (Green et al, 2019).…”
Section: Discussionmentioning
confidence: 99%